Impact of digital finance on the asset allocation of small- and medium-sized enterprises in China: Mediating role of financing constraints - Yinbo Feng; Mengmeng Meng; Gang Li (Journal of Innovation & Knowledge, 2023)
Digital finance has provided informal financial support to small- and medium-sized enterprises (SMEs) and solved the dilemma of acquiring formal financial support in emerging economies such as China. However, this may lead to structural changes in entity enterprises’ asset allocations. Based on SMEs listed on the Shenzhen Stock Exchange: Small and Medium Enterprise Board from 2011 to 2018, this study empirically examines the underlying mechanism of digital finance on the asset allocation behaviors of SMEs. The results show that digital finance enables SMEs to allocate more financial assets, thus intensifying the level of financialization of asset allocation. Furthermore, financing constraints partially mediate the relationship between digital finance and the financialization of asset allocation. Further, we investigate financialization motivation in particular and find that the impact of digital finance on the financialization of enterprises is more significant in enterprises with more investment opportunities and in areas with a speculative atmosphere. The results support that SMEs’ financial asset investment has an investment substitution motive rather than a reservoir effect. Digital finance relieves SMEs’ financing constraints and reduces their financing costs. When financing constraints are alleviated, digital finance also prevents the tendency of financialization in SMEs’ asset allocation. This study offers useful policy implications for preventing SMEs’ investment distortions in the development of digital finance.